Bank Leverage and Monetary Policy's Risk-Taking Channel : Evidence from the United States - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper ;, 2013)
We present evidence of a risk-taking channel of monetary policy for the U.S. banking system. We use confidential data on the internal ratings of U.S. banks on loans to businesses over the period 1997 to 2011 from the Federal Reserve's survey of terms of business lending. We find that ex-ante risk taking by banks (as measured by the risk rating of the bank's loan portfolio) is negatively associated with increases in short-term policy interest rates. This relationship is less pronounced for banks with relatively low capital or during periods when banks' capital erodes, such as episodes of financial and economic distress. These results contribute to the ongoing debate on the role of monetary policy in financial stability and suggest that monetary policy has a bearing on the riskiness of banks and financial stability more generally.